2004
DOI: 10.1161/01.cir.0000112641.16340.c7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Denervation Enhances Long-Term Benefit After Circumferential Ablation for Paroxysmal Atrial Fibrillation

Abstract: Background-There are no data to evaluate the relationship between autonomic nerve function modification and recurrent atrial fibrillation (AF) after circumferential pulmonary vein ablation (CPVA). This study assesses the incremental benefit of vagal denervation by radiofrequency in preventing recurrent AF in a large series of patients undergoing CPVA for paroxysmal AF. Methods and Results-Data were collected on 297 patients undergoing CPVA for paroxysmal AF. Abolition of all evoked vagal reflexes around all pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
366
5
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 876 publications
(397 citation statements)
references
References 26 publications
19
366
5
7
Order By: Relevance
“…20 However, the effectiveness of autonomic modulation as an adjunctive therapeutic strategy to catheter ablation of AF has been inconsistent. Although favorable results has been obtained by Nakagawa and Pappone et al, 21,22 others found no beneficial 23 or deleterious 24 outcomes in patients who had denervation compared to those who did not. These findings are also underlined by animal studies by Hirose et al, 25 where partial vagal denervation of the high right atrium was found to increase inducibility of AF.…”
Section: Autonomic Modulation By Neural Ablation For the Treatment Of Afmentioning
confidence: 88%
“…20 However, the effectiveness of autonomic modulation as an adjunctive therapeutic strategy to catheter ablation of AF has been inconsistent. Although favorable results has been obtained by Nakagawa and Pappone et al, 21,22 others found no beneficial 23 or deleterious 24 outcomes in patients who had denervation compared to those who did not. These findings are also underlined by animal studies by Hirose et al, 25 where partial vagal denervation of the high right atrium was found to increase inducibility of AF.…”
Section: Autonomic Modulation By Neural Ablation For the Treatment Of Afmentioning
confidence: 88%
“…246 The latter might include interruption of crucial pathways of conduction between pulmonary-atrial junctions, which play a role in sustenance of AF, reduction of the amount of mass available for the number of simultaneously circulating wavelets (atrial debulking), or partial vagal denervation by interruption of vagal stimulation from the autonomic ganglia. 109,247,248,249 Adjuvant substrate modification is targeted at patient-specific AF sources in the RA and LA. 250 AF recurrences after an initially successful AF ablation procedure are typically associated with PVI reconnection.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…An interesting correlation of CFAEs with DFs and consequently vagal ganglia was also suggested by the electroanatomical mapping performed in our study. Therefore, based also on previous observations 72,73,138,143 , ablation of vagal ganglia during AF ablation could also be advantageous.…”
Section: Resultsmentioning
confidence: 88%